Low-Cost Avoidance Behaviors are Resistant to Fear Extinction in Humans - Vervliet, Bram; Indekeu, Ellen (Frontiers in Behavioral Neuroscience, 2015)
Elevated levels of fear and avoidance are core symptoms across the anxiety disorders. It has long been known that fear serves to motivate avoidance. Consequently, fear extinction has been the primary focus in pre-clinical anxiety research for decades, under the implicit assumption that removing the motivator of avoidance (fear) would automatically mitigate the avoidance behaviors as well. Although this assumption has intuitive appeal, it has received little scientific scrutiny. The scarce evidence from animal studies is mixed, while the assumption remains untested in humans. The current study applied an avoidance conditioning protocol in humans to investigate the effects of fear extinction on the persistence of low-cost avoidance. Online danger-safety ratings and skin conductance responses documented the dynamics of conditioned fear across avoidance and extinction phases. Anxiety- and avoidance-related questionnaires explored individual differences in rates of avoidance. Participants first learned to click a button during a predictive danger signal, in order to cancel an upcoming aversive electrical shock (avoidance conditioning). Next, fear extinction was induced by presenting the signal in the absence of shocks while button-clicks were prevented (by removing the button in Experiment 1, or by instructing not to click the button in Experiment 2). Most importantly, post-extinction availaibility of the button caused a significant return of avoidant button-clicks. In addition, trait-anxiety levels correlated positively with rates of avoidance during a predictive safety signal, and with the rate of pre- to post-extinction decrease during this signal. Fear measures gradually decreased during avoidance conditioning, as participants learned that button-clicks effectively canceled the shock. Preventing button-clicks elicited a sharp increase in fear, which subsequently extinguished. Fear remained low during avoidance testing, but danger-safety ratings increased again when button-clicks were subsequently prevented. Together, these results show that low-cost avoidance behaviors can persist following fear extinction and induce increased threat appraisal. On the other hand, fear extinction did reduce augmented rates of unnecessary avoidance during safety in trait-anxious individuals, and instruction-based response prevention was more effective than removal of response cues. More research is needed to characterize the conditions under which fear extinction might mitigate avoidance.